Analysis of the Relationship between Teaching Discourse Markers to ESP Learners and Their Reading Comprehension Performance - Ana Cristina Lahuerta Martínez (Revista de Lenguas para Fines Específicos, 2015)
This study analyses the effect the teaching of discourse markers has on ESP learners' reading comprehension. Following a relevance-theoretic approach, we con- sider discourse markers as signals the speaker/writer uses to guide cooperatively his hearer's/reader's interpretative process. Therefore, they play a facilitating role. Our study intends to show that training learners in the recognition and use of DMs will improve their reading comprehension. We conclude that this instruction has a positive effect on the reading comprehension of learners of English for specific purposes.